The Relationship Analysis between Service Performances of Milk Producer Cooperative with the Dairy Farm Performance of Members - A. Asmara; Y. L. Purnamadewi; D. Lubis (Media Peternakan, 2017)
The main objective of Milk Producers Cooperative (MPC) is to provide services to the members and improve the performance of dairy farm of MPC members. The purposes of this study were: (1) to analyze dairy farm performance of MPC members, (2) to analyze performance of MPC services, and (3) to analyze the relationship between service performance of MPC with dairy farm performance of MPC members. The main data used were primary data. The analytical methods used included: descriptive analysis, profit analysis and R/C Ratio, and Chi-Square. The study showed that productivity and profitability of large-scale dairy farm was higher than small-scale. The performance of small-scale dairy farm of MPC members was relatively low both in terms of productivity and profitability. Most members judged that the performance of MPC services was good. There was a positive relationship between the MPC service performance (milk marketing, finance, technical assistance, and education/training) with the performance of dairy farm of MPC members. Coaching and more intensive services should continue to be given by the MPC to the members, especially the members with the small-scale dairy farms.